2020
DOI: 10.1155/2020/8825567
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Shoe Insole-Coated CuO-ZnO Nanocomposite Synthesized by the Sol-Gel Technique

Abstract: In this study, CuO-ZnO composite was synthesized via the sol-gel method using oxalic acid to form the medium complex and its applications in antibacterial have been conducted with B. cereus, E. coli, S. aureus, Salmonella, and P. aeruginosa. Then, nanopowder of CuO-ZnO was coated on shoe insoles and their antibacterial effect with S. aureus was tested. The nanocomposite products were characterized by XRD, XPS, SEM, TEM, and UV-Vis. The results showed that the CuO-ZnO composite has the average particle size in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…On the other hand, the SEM micrograph of CuO nanoparticles in Figure 4 b showed that they are mostly composed of uniform nanoflakes that are aggregated in a repetitive pattern, with interconnected thin flakes similar to other report [ 46 ]. Additionally, the SEM micrograph of ZnO Nps in Figure 4 c shows densely stacked short hexagonal rod-like structures that are randomly distributed similar to earlier report [ 47 , 48 ]. Furthermore, from the obtained TEM images in Figure 5 c, CuO–ZnO shows an array of spherical-shaped particles with a diameter ranging from 20–32 nm, which are somewhat arranged like a short nanorod.…”
Section: Resultssupporting
confidence: 87%
“…On the other hand, the SEM micrograph of CuO nanoparticles in Figure 4 b showed that they are mostly composed of uniform nanoflakes that are aggregated in a repetitive pattern, with interconnected thin flakes similar to other report [ 46 ]. Additionally, the SEM micrograph of ZnO Nps in Figure 4 c shows densely stacked short hexagonal rod-like structures that are randomly distributed similar to earlier report [ 47 , 48 ]. Furthermore, from the obtained TEM images in Figure 5 c, CuO–ZnO shows an array of spherical-shaped particles with a diameter ranging from 20–32 nm, which are somewhat arranged like a short nanorod.…”
Section: Resultssupporting
confidence: 87%
“…CuO–ZnO NCs can be fabricated by various methods including precipitation, sol–gel, solvothermal, electrospinning, photodeposition, microwave-assisted, electrochemical, thermal decomposition, and spray pyrolysis . Among these methods, a microwave-assisted method has several benefits in comparison to conventional heating methods, such as fast reactions, uniform particle size distribution, high yield, and highly pure nanomaterials .…”
Section: Introductionmentioning
confidence: 99%